Adab-adab Mu’allim (Pengajar) dan Muta’alim (Pelajar) Perspektif Imam an-Nawawi dalam Kitab at-Tibyan fi Adabi Hamalatil Qur’an dan Relevansinya dengan Pendidikan Adab Masa Kini - Mudzkirah, Mudzkirah; Rivauzi, Ahmad (ANWARUL, 2024)
The phenomenon of declining student ethics in today's educational environment reflects a serious challenge among education leaders, teachers, and students. This has implications for the quality of education. The damage to ethics, manners, and behavior is concerning, indicating a lack of attention to moral education in the present era. The aim of this research is to describe Mu’allim (teacher) and Muta’allim (student) according to Imam An-Nawawi, and to explain the relevance of these etiquettes to moral education in the current era. The research method employed is qualitative, specifically the library research type. The research findings are expected to serve as a guide for educators and learners in maintaining proper conduct in the educational environment. Imam An-Nawawi's thoughts on the ethics of teachers and students prove to be relevant to contemporary moral education. The implementation of moral conduct in the education sector needs attention to uphold moral values and ethics, shape the character of the younger generation, and prevent moral damages detrimental to education.